Uveitis Is a Risk Factor for Juvenile Idiopathic Arthritis' Significant Flare in Patients Treated With Biologics - Kostik, Mikhail M.; Gaidar, Ekaterina V.; Sorokina, Lubov S.; Avrusin, Ilya S.; Nikitina, Tatiana N.; Isupova, Eugenia A.; Chikova, Irina A.; Korin, Yuri Yu.; Orlova, Elizaveta D.; Snegireva, Ludmila S.; Masalova, Vera V.; Dubko, Margarita F.; et al. (Frontiers in Pediatrics, 2022)
Objectives Uveitis is the most frequent extra-articular manifestation of juvenile idiopathic arthritis (JIA). Our study is aimed to evaluate the possible difference in arthritis course depending on uveitis presence in patients with JIA, treated with biologics. Methods From our database of patients with JIA treated with biologics, we extracted patients to whom the first agent was administrated with or without MTX. The exclusion criteria included treatment with current systemic corticosteroids, infliximab, rituximab, observation period <3 years, and no missing data. After selection, 175 patients were eligible for analysis. We evaluated clinically significant flare with joint involvement (which required change of biologic or non-biologic DMARD) and time to flare. We compared two groups: (i) patients with uveitis (n = 32) and (ii) patients without uveitis (n = 143). For statistical analysis, we used Cox's regression models, the log-Rank test, x2 test, and the Mann–Whitney test. Results There was no difference in gender distribution and achievement of arthritis remission between groups. Patients in the non-uveitis group predominantly received etanercept (64.3%). In the uveitis group, the most prescribed biologic agent was adalimumab (71.9%). The presence of uveitis increased the risk of JIA flare, OR = 3.8 (95% CI: 1.7; 8.7), and the cumulative probability of joint flare, RR = 4.5 (95% CI: 1.7; 12.1), p =.003, after adjustment on methotrexate, RR = 3.1 (1.6; 6.), p =.0008. In the subgroup of patients treated with adalimumab, the absence of methotrexate increased the cumulative probability of flare [RR = 6.5 (95% CI: 1.4; 31.1), p = 0.02]. Conclusion The presence of uveitis proved to be a risk factor in JIA flare. Methotrexate can decrease the cumulative flare probability. Further trials are required.